Continuous Directional Water Transport on Integrating Tapered Surfaces. Issue 9 (16th March 2020) - Feng, Shile; Wang, Qianqian; Xing, Yan; Hou, Yongping; Zheng, Yongmei
Abstract: Controllable directional transport of droplets is ubiquitous in nature and essential in many practical applications, which is based on disparity of physical structures and surface energy. Despite vast innovations in liquid transport strategies to generate liquid transport at a wide spectrum and various scales, the transport distance is limited due to the drawback of unwanted pinning of contact lines. Here, a continuous, directional, and long‐range transport system of fog droplets on integrating tapered surface inspired by spider silk and butterfly wing is reported. A new phenomenon occurs at the joint of integrating tapered surface: liquid film switches periodically between convex‐continuous and concave‐intermittent, which promotes the rapid surface reconstruction and fog droplet collection. The transport dynamics of fog droplets and rapid surface reconstruction facilitate highly effective water harvesting task. Abstract : A high efficiency water harvesting system is achieved on integrating tapered surface with physical tapered structure and chemical wetting gradient. Both continuous, directional, long‐range transport of fog droplets and rapid surface reconstruction are achieved. This work provide a novel design concept for liquid transport, which can be applied in both micro‐fluid setting and water harvesting systems.